2015
DOI: 10.1155/2015/504567
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Salidroside on Mitochondrial Functions against Exertional Heat Stroke-Induced Organ Damage in the Rat

Abstract: Exertional heat stroke (EHS) results in a constellation of systemic inflammatory responses resulting in multiorgan failure and an extremely high mortality. The present study was designed to evaluate the protective effects of salidroside on EHS by improving mitochondrial functions in the rat model. Liver and heart mitochondria were observed by transmission electron microscopy and mitochondrial membrane potential (ΔΨm) was detected by a fluorescent probe. Intramitochondrial free Ca2+ concentration, mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…Salidroside (Sal, 2-(4-hydroxyphenyl)ethyl β -D-glucopyranoside, C 14 H 20 O 7 ) is mainly extracted from Rhodiola rosea L., which grows at high altitude localities and usually is used as one of the herbal drugs in worldwide [ 20 ]. Sal has been shown to have numerous pharmacological effects, such as antioxidant effects [ 21 , 22 ], antiapoptosis effects [ 23 ], and maintenance of mitochondrial function [ 24 ]. Our paper recently found that Sal protected DA neurons against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine- (MPTP-)/1-methyl-4-phenyl-pyridinium- (MPP + -) induced toxicity in a dose-dependent manner through modulation of the ROS-NO related mitochondrial pathway both in vivo and in vitro [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salidroside (Sal, 2-(4-hydroxyphenyl)ethyl β -D-glucopyranoside, C 14 H 20 O 7 ) is mainly extracted from Rhodiola rosea L., which grows at high altitude localities and usually is used as one of the herbal drugs in worldwide [ 20 ]. Sal has been shown to have numerous pharmacological effects, such as antioxidant effects [ 21 , 22 ], antiapoptosis effects [ 23 ], and maintenance of mitochondrial function [ 24 ]. Our paper recently found that Sal protected DA neurons against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine- (MPTP-)/1-methyl-4-phenyl-pyridinium- (MPP + -) induced toxicity in a dose-dependent manner through modulation of the ROS-NO related mitochondrial pathway both in vivo and in vitro [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary intake of SDS has been shown to protect PC12 cells against H 2 O 2 -induced apoptosis [ 33 ] and HaCAT cells against UVB-mediated oxidative damage [ 34 ]. SDS has also been reported to alleviate oxidative stress in the liver with non-alcoholic steatohepatitis in rats [ 35 ], to prevent kainic acid-induced status epilepticus via suppressing oxidative stress and diabetes-induced oxidative stress in mice [ 36 , 37 ], and to protect mitochondria against exertional heat stroke-induced organ damage and retinal endothelial cells against hydrogen peroxide-induced injury via modulating oxidative status and apoptosis in rats [ 38 , 39 ]. The main findings of our study are that late-onset SDS administration does not reduce the body weight and length of aging N. guentheri , but it is able to decrease the age-related markers and increase the median and maximum lifespans of the fish.…”
Section: Discussionmentioning
confidence: 99%
“…Cyt C is then translocated into the cytosol and caspase-3/9 is activated to induce cell apoptosis ( 33 , 34 ). The depolarization of ∆ψm, mitochondria swelling, the increase of malondialdehyde and ROS, and the decrease of superoxide dismutase are the characteristics of mitochondrial dysfunction ( 35 ). Zhu et al have demonstrated that allicin provides protection against spinal cord ischemia/reperfusion injury in rabbits through enhancing antioxidant enzyme activities and improving mitochondrial function ( 36 ).…”
Section: Discussionmentioning
confidence: 99%